2020
DOI: 10.1039/d0ce00347f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a finger-like MoS2@VS2 micro–nanocomposite with enhanced field emission performance

Abstract: A MoS2@VS2 micro–nanocomposite showed enhanced field emission properties benefiting from the synergy of the two materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Changqing Song et al have reported highly efficient FE properties of a novel layered VS 2 /ZnO nanocomposite and flexible VS 2 nanosheet emitters . Very recently, synthesis of a finger-like MoS 2 @VS 2 micro–nanocomposite with enhanced FE performance has been reported . The group working from Pune University has carried out studies on FE performance of variety of 2D TMD nanostructures and nanocomposites. The group has studied FE behavior of In 2 Se 3 nanowires synthesized by simple thermal evaporation in a Quartz tube furnace …”
Section: Introductionmentioning
confidence: 99%
“…Changqing Song et al have reported highly efficient FE properties of a novel layered VS 2 /ZnO nanocomposite and flexible VS 2 nanosheet emitters . Very recently, synthesis of a finger-like MoS 2 @VS 2 micro–nanocomposite with enhanced FE performance has been reported . The group working from Pune University has carried out studies on FE performance of variety of 2D TMD nanostructures and nanocomposites. The group has studied FE behavior of In 2 Se 3 nanowires synthesized by simple thermal evaporation in a Quartz tube furnace …”
Section: Introductionmentioning
confidence: 99%
“…The (002) peak of MoS 2 and the (001) peak of VS 2 appeared almost at the same 2θ value (V and M stand for VS 2 and MoS 2 , respectively); thereby, a sharp peak appeared, exhibiting the successful formation of the heterostructure. Moreover, the crystal growth of the heterostructure occurred along the Z (axis) direction as confirmed by the intense peak at the lower 2θ position. , Except for the crystal growth plane, the heterostructure does not show intense peaks, indicating that the crystallinity is monitored by the heterostructure growth. As a result, more edges and active sites are exposed to the formation of heterostructures, significantly enhancing the catalytic performance for HER. Furthermore, inert basal planes can be exposed during heterostructure growth via lateral and vertical epitaxy mechanisms, indicating the improved HER activity.…”
Section: Resultsmentioning
confidence: 90%
“…The percentage area of the V 3+ state was higher in VMS1 than in VMS2, indicating the formation of dangling sulfur atoms, which can act as active sites for hydrogen absorption and desorption as confirmed from Figure S1d. , Interestingly, the Mo 3d peaks for all the VS 2 /MoS 2 heterostructures depicted a shift toward a lower binding energy compared with pure MoS 2 . The observed peak shifts demonstrated that the electrons may transfer from VS 2 nanosheets to MoS 2 nanopetals as the former has a smaller work function and thereby a strong coupling effect between VS 2 and MoS 2 was formed at the heterostructure interface. ,, Moreover, the strong electronic interaction between VS 2 and MoS 2 in the heterostructure provided a conducting architecture, and therefore, the electrochemical performance was improved. Figure a–c shows the two characteristic peaks of S 2– species, which correspond to the S 2p3/2 and S 2p1/2, with a spin-orbit splitting of 1.2 eV. The XPS results were in good agreement with the successful formation of the heterostructure as reported in the literature. , Moreover, the obvious binding energy shifts for Mo 3d, V 2p, and S 2p XPS spectra suggested a strong electronic interaction between the MoS 2 and VS 2 within the different compositions of the heterostructures.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations